The Effect of Clinical Pathway Socialization with Explicit Instruction Methods on Nurse Compliance in the Implementation of the COVID-19 Clinical Pathway - Twistiandayani, Retno; Ayatulloh, Daviq; Kinarti, Meli Candra (Universitas Airlangga, 2022)
Introduction: Clinical pathway is an integrated concept in the form of preventing unnecessary care, medication errors or other harmful incidents. Strategies to improve nurse compliance on clinical pathways have widely implemented. However, the effectiveness was found to be inconsistent. This study aimed to determine the effect of the socialization of the explicit instruction method on nurse compliance in the implementation of the COVID-19 clinical pathway. Method: This research method applied a pre-experimental research design with one group pretest-posttest design. The sampling technique used total sampling with a sample of 24 respondents from September to November 2021. The dependent variable was the socialization of the clinical pathway with the explicit instruction method.The independent variable was nurse compliance in the implementation of the COVID-19 clinical pathway. Data was taken by means of observation using a clinical pathway checklist instrument which was then analyzed using the Wilcoxon Signed Ranks Test with sig p <0.05. Results: the results of this study prove that there was a significant effect of providing socialization. Explicit instruction method on nurse compliance showed a significant impact on the implementation of the COVID-19 clinical pathway with a value (p = 0.008) with a compliance rate of 83%. Conclusions: Compliance with the established clinical pathway increase quality of health care service. This study found explicit instruction method effectively increase nurse compliance on the COVID-19 clinical pathway. Studies measuring explicit instruction in combination with other methods that strengthen nurse compliance with clinical pathway are crucial to be conducted.